Small area estimation for the price of habitation transaction: comparison of different uncertainty measures of temporal EBLUP - Pereira, Luis Nobre (2012)
Local level planning requires statistics for small areas, but normally due to cost or logistic constraints, sample surveys are often planned to provide reliable estimates only for large geographical regions and large subgroups of a population.